Pre Analysis of Personal and Professional Factors Affecting Accounting Students’ Career Interest in Public Accountant: Personal and Professional Factors - Setiana, Sinta; Wijaya, I Nyoman Agus (Institut Bisnis dan Informatika Kesatuan, 2025)
The Public Accountant profession in Indonesia faces a shortage of professionals, necessitating an understanding of factors influencing students’ career interest. This study aims to examine the effect of personal factors, measured as the Conventional personality type, and professional factors, including labor market considerations and social values, on final-year accounting students’ interest in becoming public accountants. A quantitative approach was employed, using a questionnaire distributed to 60 final-year students at an Indonesian university. Data were analyzed using multiple linear regression to test the individual and combined effects of personal and professional factors. The findings reveal that personal factors have a significant positive effect on interest, while professional factors exhibit a significant negative effect, possibly due to perceived work pressure. Together, these factors explain 99.2 percent of the variance in interest, indicating a robust model. The study concludes that personal factors strongly drive interest in Public Accountant, whereas professional factors deter it, highlighting the need for universities to use personality assessments in career counseling and for firms to address negative perceptions to attract talent. Future research should explore broader samples and additional factors to enhance career interest.